New for Ukraine species of Scutellinia (Pyronemataceae, Pezizales) from the Svydovets mountain range (Carpathian biosphere reserve) - Dzhagan, V.V.; Scherbakova, Yu.V. (Український ботанічний журнал, 2013)
The article reports on three new for Ukraine records of
Scutellinia collected in the Svydovets Mountain Range (Carpathian
Biosphere Reserve): S. crinita (Bull.) Lambotte, S. crucipila (Cooke et W. Phillips) J. Moravec, and S. pseudotrechispora (J. Schröt.)
Le Gal. Brief descriptions, localities, data on general distribution
and original illustrations are provided. Повідомляється про три нові для України види роду Scutellinia, зібрані на території Свидовецького заповідного масиву (Карпатський біосферний заповідник): S. crinita (Bull.) Lambotte, S. crucipila (Cooke et W. Phillips) J. Moravec і S. pseudotrechispora (J. Schröt.) Le Gal. Подано їхні короткі описи, інформація про місцезнаходження, загальне поширення, а також оригінальні ілюстрації. Сообщается о трех новых для Украины видах рода Scutellinia, собранных на территории Свидовецкого заповедного массива (Карпатский биосферный заповедник): S. cri nita (Bull.) Lam botte, S. crucipila (Cooke et W. Phillips) J. Mo ra vec и S. pseu dotrechispora (J. Schröt.) Le Gal. Приведены их краткие описания, данные об местонахождении и общем распространении, а также оригинальные иллюстрации.